A review of predation as a limiting factor for bird populations in mesopredator‐rich landscapes: a case study of the UK. (22nd May 2018) - Roos, Staffan; Smart, Jennifer; Gibbons, David W.; Wilson, Jeremy D.
ABSTRACT: The impact of increasing vertebrate predator numbers on bird populations is widely debated among the general public, game managers and conservationists across Europe. However, there are few systematic reviews of whether predation limits the population sizes of European bird species. Views on the impacts of predation are particularly polarised in the UK, probably because the UK has a globally exceptional culture of intensive, high‐yield gamebird management where predator removal is the norm. In addition, most apex predators have been exterminated or much depleted in numbers, contributing to a widely held perception that the UK has high numbers of mesopredators. This has resulted in many high‐quality studies of mesopredator impacts over several decades. Here we present results from a systematic review of predator trends and abundance, and assess whether predation limits the population sizes of 90 bird species in the UK. Our results confirm that the generalist predators Red Fox ( Vulpes vulpes ) and Crows ( Corvus corone and C. cornix ) occur at high densities in the UK compared with other European countries. In addition, some avian and mammalian predators have increased numerically in the UK during recent decades. Despite these high and increasing densities of predators, we found little evidence that predation limits populations of pigeons, woodpeckers and passerines, whereas evidence suggests that ground‐nesting seabirds, waders and gamebirds can be limited by predation. Using life‐history characteristics of prey species, we found that mainly long‐lived species with high adult survival and late onset of breeding were limited by predation. Single‐brooded species were also more likely to be limited by predation than multi‐brooded species. Predators that depredate prey species during all life stages (i.e. from nest to adult stages) limited prey numbers more than predators that depredated only specific life stages (e.g. solely during the nest phase). The Red Fox and non‐native mammals (e.g. the American Mink Neovison vison ) were frequently identified as numerically limiting their prey species. Our review has identified predator–prey interactions that are particularly likely to result in population declines of prey species. In the short term, traditional predator‐management techniques (e.g. lethal control or fencing to reduce predation by a small number of predator species) could be used to protect these vulnerable species. However, as these techniques are costly and time‐consuming, we advocate that future research should identify land‐use practices and landscape configurations that would reduce predator numbers and predation rates.